The Influence of Multimedia Assisted Inquiry Learning Methods on My Heroes' Theme of Critical Thinking Skills and Learning Outcomes of Class IV Students of Elementary School - Purwanita, Yulis; Riyanto, Yatim; Suyanto, Totok (Universitas Malikussaleh, 2019)
Researchers were interested in applying Inkuiry's learning method to teach my hero material. The media is called